Advances in Discontinuous Numerical Methods and Applications in Geomechanics and Geoengineering. - Zhao, Jian (CRC Press, 2012)
Rocks and soils can behave as discontinuous materials, both physically and mechanically, and for such discontinuous nature and behaviour there remain challenges in numerical modelling methods and techniques. Some of the main discontinuum based numerical methods, for example the distinct element method (DEM) and the discontinuous deformation analysis (DDA), are associated with geomechanics and geoengineering. Discontinuous numerical methods have been widely applied in geoengineering related to civil, mining, hydropower and petroleum engineering. There are many good examples of the use of UDEC/3.